Pengaruh Jenis Pupuk Kandang dan Jarak Tanam terhadap Pertumbuhan Gulma dan Hasil Jagung Manis - ARI MAYADEWI, NI NYOMAN (AGRITROP, 2007)
The experiment aimed to find out the effect of different manure materials and proper corn plant spacing on weedgrowth and sweet corn yield. The experiment was conducted in Agricultural Training, Research and Development(ATRD), Gadjah Mada University. The experiment was a factorial experiment in a split plot design with threereplications. As the main treatment was different manuring, consisting of (1) no manure, (2) cow manure, (3) goatmanure, and (4) chicken manure. Plant spacing consisting of : (1) 100 cm x 20 cm, (2) 50 cm x 40 cm, and (3) 80cm x 25 cm, served as sub treatments. The results showed a significant interaction between manuring and plantspacing with respect to weed growth and sweet corn yield. The lowest weed dry weight when corn plants werespaced at 50 cm x 40 cm, and chicken manuring was given. Chicken manuring produced the highest ear yield,162.43 g/plant; mean while, plant spacing of 50 cm x 40 cm produced the highest ear yield, amounting to 154.44g/plant. Chicken manuring to sweet corn plants spaced at 50 cm x 40 cm gave the largest marketable ears, 11.567t/ha.